Manganese and copper-coated nickel oxide nanoparticles synthesized from Carica papaya leaf extract induce antimicrobial activity and breast cancer cell death by triggering mitochondrial caspases and p53 - Alzahrani, Badr; Elderdery, Abozer Y.; Alsrhani, Abdullah; Alzerwi, Nasser A.N.; Althobiti, Maryam Musleh; Rayzah, Musaed; Idrees, Bandar; Elkhalifa, Ahmed M.E.; Alabdulsalam, Abdulrahim A.; Alsultan, Afnan; Bakhsh, Ebtisam; ALSuhaymi, Naif; et al. (Walter de Gruyter GmbH, 2024)
In the present work, manganese–copper co-infused nickel oxide nanoparticles (MnCu co-doped NiO NPs) were formulated via a green process using Carica papaya extract. The MnCu co-doped NiO NPs were characterized by X-ray diffraction (XRD), UV–Vis, Fourier transform infrared, field emission scanning electron microscope, energy dispersive X-ray analysis, and photoluminescence (PL) spectrum. The XRD pattern demonstrated that synthesized MnCu codoped NiO NPs exhibit cubic structure. On the PL spectrum, various surface defects were identified. MnCu co-doped NiO NPs exhibited ferromagnetic properties at 37°C. The antimicrobial activity of green synthesis MnCu co-doped NiO NPs against human pathogens (Escherichia coli, Streptococcus pneumoniae, Bacillus megaterium, Bacillus subtilis, Shigella dysenteriae, Pseudomonas aeruginosa) and Candida albicans as fungal strains were demonstrated. The MnCu co-doped NiO NPs treatment considerably reduced MDA-MB-231 cell viability while not disturbing HBL-100 cell viability. Different fluorescent staining analyses revealed that MnCu co-doped NiO NPs induced nuclear and mitochondrial damage to improve free radical production, altering mitochondrial membrane protein potential, which led to apoptotic cell death in MDA-MB-231 cells. The MnCu co-doped NiO NP treatment enhanced pro-apoptotic protein expression and inhibited the cell cycle at the S phase in MDA-MB-231 cells. This makes it easy, cheap, and environmentally friendly to make MnCu co-doped NiO NPs using C. papaya extract, which has excellent antimicrobial properties.